the worldlihood of Knowledge and some of its implications Based on Mulla Sadra’s Theosophy - meisam vaseqi; mohammad taqi chavoshi (حکمت اسرا, 2014)
The study of the logics governing knowledge can be considered as one of the fundamental issues in philosophy. Moreover, various approaches of different philosophical schools of thoughts to this issue bring about different implications for those sub-issues that are discussed based on it. The present paper claims that the worldlihood of knowledge is an outcome that stems from the principles of Mulla Sadra’s theosophy concerning knowledge. The authors seek to explain how man becomes able to attain further knowledge in terms of their specific existential connection to the known and their own acquired knowledge, by concentrating on the status of the knower in Mulla Sadra's views and some philosophical principles concerning that, such as the trans-substantial motion and the unity of the knower, the known and the knowledge. Among other sub-issues discussed based on this idea are: proving the social world, which concerns about the possibility of mutual understanding based on this belief, and the possibility of the religious knowledge, which has attended to this perspective with a novel view of the religious knowledge, employing Ayatollah Javadi Amoli’s approach to this issue.